Pengaruh Kualitas Pelayanan, Persepsi Harga dan Citra Merek Terhadap Kepuasan Pelanggan (Survei pada Pelanggan PT. Kimia Farma Apotek Domisili Kota Tasikmalaya) - Momy Damayanti; Nadya Zahra Virliana; Tika Widian Prahasti (EKOBIMA, 2024)
The purpose of this research was to determine and analyze (a) the service quality, price perception, brand image and customer satisfaction in PT. Kimia Farma Apotek Domicile in the city of Tasikmalaya. (b) The effect of service quality, price perception, and brand image of the customer satisfaction PT. Kimia Farma Apotek Domicile in the City of Tasikmalaya either partially or simultaneously. The method used is survey method. The technique of collecting data through interviews, observation and questionnaires. The sampling technique used by simple random sampling with customers populations PT. Kimia Farma Apotek Domicile in the City of Tasikmalaya as many as 340 respondents. The data have been obtained were analyzed using path analysis. The results of the overall rating classification for service quality are included in good classification, while for price perception is included in very good classification, and for brand image is included in good classification. Based on the results of the analysis showed that service quality, price perception, and brand image significantly influence customer satisfaction PT. Kimia Farma Apotek Domicile in the City of Tasikmalaya both partially and simultaneously.